Review of the Effects of the Abuse of Narcotics, Psychotropics, and Other Addictive Substances - Samsul, Erwin; Amiruddin, Widya Salsabila Putri; Hasanah, Fitri; Wulandari, Tiara Sahfitri; Basongan, Oktariani; Syam, Mawar Inrian; Yusuf, Muhammad; Gala, Kretentia Aprilia; Rachmawati, Nova Sri (Journal of Pharmaceuticals and Natural Sciences, 2025)
The purpose of this study was to identify the forms of drug abuse and evaluate the impact of drug abuse in the community. This research uses a qualitative approach and is a descriptive study. This research uses the narrative literature method. This review process used the narrative review method by collecting literature from various sources, including scientific journals, government reports, and relevant conference articles, with the inclusion criteria being articles published within the last 10 years, in Indonesian or English, and discussing topics related to the impact or intervention of drug abuse. In the initial stage of searching journal articles, 17,083 articles from 2019-2024 with identified keywords such as "Drug Abuse", "Substance Abuse Cases", and "Psychotropic Abuse" were found. Of the collected articles, 25 journal articles met the criteria. The analysis was done descriptively to synthesize information based on certain categories, such as health impact and policy effectiveness. Based on the literature, the most common drug abuse included mephedrone, trihexyphenidil, LSD, and amphetamine. The results of this study indicate that the effects of drug use include agitation (30%), addiction (20%), hallucinations (60%), aggression (50%), euphoria (70%), and disorientation (50%). It is recommended to avoid using drugs because it can harm the body's condition.